Do community scorecards improve utilisation of health services in community clinics: experience from a rural area of Bangladesh - S. M. A. Hanifi; Aazia Hossain; Asiful Haidar Chowdhury; Shahidul Hoque; Mohammad Abdus Selim; Shehrin Shaila Mahmood; Abbas Bhuiya (BMC, 2020)
Abstract Background The government of Bangladesh initiated community clinics (CC) to extend the reach of public health services and these facilities were planned to be run through community participation. However, utilisation of CC services is still very low. Evidence indicates community score card is an effective tool to increase utilisation of services from health facility through regular interface meeting between service providers and beneficiary. We investigated whether community scorecards (CSC) improve utilisation of health services provided by CCs in rural area of Bangladesh. Methods This study was conducted from December 2017 to November 2018. Three intervention and three control CCs were selected from Chakaria, a rural sub-district of Bangladesh. CSC was introduced with the Community Groups and Community Support Groups in intervention CCs between January to October 2018. Data were collected through observation of CCs during operational hours, key informant interviews, focus group discussions, and from DHIS2. Utilisation of CC services was compared between intervention and control areas, pre and post CSC intervention. Results Post CSC intervention, community awareness about CC services, utilisation of clinic operational hours, and accountability of healthcare providers have increased in the intervention CCs. Utilisation of primary healthcare services including family planning services, antenatal care, postnatal care and basic health services have significantly improved in intervention CCs. Conclusion CSC is an effective tool to increase the service utilization provided by CCs by ensuring community awareness and participation, and service providers' accountability. Policy makers and concerned authorities may take necessary steps to integrate community scorecard in the health system by incorporating it in CCs.